Indentation-Induced Structural Changes in Vitreous Silica Probed by in-situ Small-Angle X-Ray Scattering - Fuhrmann, Sindy; de Macedo, Guilherme N. B. M.; Limbach, René; Krywka, Christina; Bruns, Sebastian; Durst, Karsten; Wondraczek, Lothar (Frontiers in Materials, 2020)
The transient (or permanent) structural modifications which occur during local deformation of oxide glasses are typically studied on the basis of short-range data, for example, obtained through vibrational spectroscopy. This is in contrast to macroscopic observations, where variations in material density can usually not be explained using next-neighbor correlations alone. Recent experiments employing low-frequency Raman spectroscopy have pointed-out this issue, emphasizing that the deformation behavior of glasses is mediated through structural heterogeneity and drawing an analogy to granular media. Here, we provide additional support to this understanding, using an alternative experimental method. Structural modification of vitreous silica in the stress field of a sharp diamond indenter tip was monitored by in-situ small-angle X-ray scattering. The influenced zone during loading and after unloading was compared, demonstrating that changes in the position of the first sharp diffraction peak (FSDP) directly in the center of the indent are of permanent character. On the other hand, variations in the amplitude of electron density fluctuations appear to fully recover after load release. The lateral extent of the modifications and their relaxation are related to the short- to intermediate-range structure and elastic heterogeneity pertinent to the glass network. With support from Finite Element Analysis, we suggest that different structural length scales govern shear and isotropic compaction in vitreous silica.